Comparison of Umbilical Cord blood Bilirubin (UCB) and Bilirubin Albumin Ratio (BAR) in Predicting Neonatal Hyperbilirubinemia: A Prospective Observational Study - T Rehna; KP Shiyas (Indian Journal of Neonatal Medicine and Research, 2021)
Introduction: Hyperbilirubinemia is a commonly encountered medical condition in neonates. It becomes problematic when the levels of bilirubin raises to abnormally high values leading on to neurological problems. Bilirubin Albumin Ratio (BAR) can be used as a prediction tool for subsequent hyperbilirubinemia in neonates thereby helping in early institution of therapy. Aim: To compare Umbilical Cord blood Bilirubin (UCB) and the BAR in predicting neonatal hyperbilirubinemia. Materials and Methods: This prospective observational study was conducted in the neonates born at Al-Azhar Medical College, Thodupuzha, Kerala, India, from April 2020 to February 2021. After obtaining clearance from Institute Research Committee and Institute Ethical Committee, 1025 healthy term babies were included in the study. After an informed consent from either of the parent, cord blood was sent for bilirubin, albumin and the blood group estimation. Babies were examined daily for any development of jaundice for five days or till discharge. Venous blood was sent for bilirubin estimation if clinical icterus was noted by Kramer’s rule any time after birth or at 72 hours. If hyperbilirubinemia was detected, treatment was instituted. Two cut-offs for UCB-2 and 2.5 mg/dL and two cut-offs for BAR 0.59 and 0.69 were correlated with the neonatal hyperbilirubinemia using Pearson correlation and Chi-square test. The p-value <0.05 was taken as statistically significant. The cut-off values for cord bilirubin and BAR that could predict hyperbilirubinemia was also obtained from Receiver Operating Curve (ROC). Results: Of the 1025 babies studied, hyperbilirubinemia was detected in 246 babies (24%). Babies with higher UCB and BAR had statistically significant risk of neonatal hyperbilirubinemia. UCB >2 mg/dL and 2.5 mg/dL and BAR 0.59 and 0.69 were found to strongly correlate with the risk of hyperbilirubinemia. Higher the UCB and BAR, higher the risk. On ROC analysis, cut-off points for UCB and BAR were 2 mg/dL and BAR >0.59 respectively. A highly significant correlation was found between UCB and hyperbilirubinemia as well as between BAR and hyperbilirubinemia with a p-value <0.001. Among UCB and BAR, UCB is found to have better sensitivity and specificity than BAR with cut-off 2 mg/dL with better sensitivity of 75.2% and cut-off 2.5 mg/dL with a better specificity of 89.6%. Conclusion: UCB and BAR are strong predictors of neonatal hyperbilirubinemia with UCB a better predictor than BAR.